Upstep of low tone in Njyem and Register Tier Theory - (:unkn) unknown (My University, 2007)
The phenomenon of tonal upstep has been described in several languages. However, the focus has been on the upstep of high tone only. In this paper, our research on tone in Njyem, a Bantu language spoken in the Eastern Province of Cameroon and in Souanké, north of the Republic of the Congo, presents an interesting case of upstep of low tone. The analysis of this phenomenon leads to the conclusion that the facts of upstep of low tone can receive an insightful and explanatory account within Register Tier Theory (RTT).
Keywords: African Research